IMPACT OF CARS WITH 25 TF/AXLE LOAD ON THE TRACK CONDITION - О. M. Patlasov; E. M. Fedorenko (Nauka ta progres transportu, 2019)
Purpose. The research is aimed at determining changes in the state of the geometrical parameters of the railway track, depending on the passing tonnage in dynamic interaction with the 25 tf/axle load rolling stock. Methodology. For data acquisition, the authors carried out a statistical analysis of the indicators of digital measurements of the track condition by KVL-P track-measuring cars. Using the program of calculating the mean-square deviation of the geometric parameters of the track, the deviation of the track parameters within the test sections was estimated. Findings. During the observation period it was found that on average the intensity of track strain accumulation increases. However, according to the results of the factor dispersion analysis with 0.95 probability, it is impossible to unequivocally state the impact of the factor of using the cars with an axial load of up to 25 tf/axle on the deterioration of the track condition parameters. Herewith it should be noted that the share of cargo carried in the cars with axial load of up to 25 tf/axle during the observation period was less than one per cent. According to the values of the mean-square deviation, the state of the geometrical parameters of the track and their predicted changes were estimated, which showed that the increased axial load will lead to decreased life of the rails, which are the most expensive elements of the track structure, shortened service life of the railroad switches and increased labor costs for workers involved in track repair and maintenance. The corresponding reduction of inter-repair periods, which corresponds to the standards, is projected. In order for heavy-duty wagons not to destroy the infrastructure, there must be at least two limitations: by the types of goods transported and by the speed of movement. Originality. The authors conducted a study to assess the impact of cars with 25 tf/axle load on the state of the geometric parameters of the railway track and proposed solutions to the issue of introducing the 25 tf/axle load rolling stock in Ukraine. Practical value. On the basis of the obtained results it is possible to estimate the impact of the axial load on the intensity of the track condition changes and to predict the reduction of inter-repair periods in connection with the track deterioration and in accordance with the train speed restriction.